Failure analysis of hydrothermal synthesis for spinel manganese–cobalt oxide. Issue 43 (14th October 2022) - Li, Zhao; Ren, Zhiguo; Zhao, Yuanxin; Wu, Shuaijin; Yao, Yingying; Ren, Xiaochuan; Zhu, Daming; Li, Xiaolong; Zou, Jianxin
Abstract : We synthesize spinel manganese–cobalt oxide through hydrothermal method, while the final synthetic sample is neither MnCo2 O4 nor MnCo2 O4.5, but a two-phase coexistence of Co3 O4 and Mn 3+/4+ -doped Co3 O4 . Abstract : Spinel Co3 O4 is one of the important functional materials applied in many fields such as electrochemical catalysis and energy storage. Compared with pure Co3 O4, the activity of the catalytic sites increases when the Co 2+ /Co 3+ located in tetra-/octahedral sites was substituted by Mn 2+ /Mn 3+ . In this work, we designed a molar feed ratio of 1 : 2 of bivalent Mn and Co sources and utilized a hydrothermal method to synthesize a spinel manganese–cobalt oxide (Mn–Co–O), however, we found that the atomic ratio of the Mn–Co–O precursor after hydrothermal synthesis was just 0.08 instead of 0.5. Moreover, synchrotron radiation X-ray diffraction analyses combined with the electron diffraction data confirm that the final synthetic sample is neither MnCo2 O4 nor MnCo2 O4.5, and the sample after calcining the precursor is identified as a two-phase coexistence of pure cubic Co3 O4 and Mn-doped cubic Co3 O4 . Furthermore, X-ray absorption spectroscopy (XAS) results reveal that Mn 2+ has been oxidized to Mn 3+/4+ after hydrothermal processing, while Co 2+ still remains unchanged. Finally, XAS and Raman spectra jointly illustrate that Co 2+ hydrate transforms to a spinel Co3 O4 structure consisting of Co 2+ and Co 3+ after calcining the precursor. This work indicates that the inconsistent and incomplete reaction between Mn 2+ and Co 2+ during hydrothermal processing leads to the failure of synthesizing a spinel manganese–cobalt oxide using a Mn : Co molar feed ratio.